Maximizing Revenue : an in-depth Analysis of Tobacco Excise, Ethyl Alcohol Excise, and Excise Revenue - Lenny, Lenny (Owner : Riset dan Jurnal Akuntansi, 2024)
Excise revenue's contribution to state revenue is intimately linked to its inclusion in the central government's financial report. The Directorate General of Customs collects excise duties on ethyl alcohol, tobacco goods, and ethyl alcohol-containing beverages, which are then reported to the federal government in financial reports. While there is a lot of research on tobacco excise, there isn't much on excise duties on ethyl alcohol, which is the subject of this study. The research technique is descriptive-quantitative, with secondary data sourced from central government financial reports from 2006 to 2022 and processed with SPSS software. Three hypotheses are tested, with the first indicating that tobacco excise has a considerable impact on excise revenue. The second hypothesis asserts that excise levies on ethyl alcohol have little impact on excise revenue. However, the final hypothesis is accepted, suggesting that tobacco excise and excise levies on ethyl alcohol have a significant impact on excise revenue, as demonstrated by a high R square value.